Atomistic models and time-dependent simulations of spin dynamics in isolated and current-carrying systems - Pertsova, Anna (Trinity College (Dublin, Ireland). School of Physics, 2012)
Understanding and ultimately controlling the dynamics of electrons and their spins is an important aspect of spin-based electronics. Recent experimental advances open up new possibilities for probing spin dynamics with very high spatial and temporal resolution, i.e. in atomic-sized systems and at sub-picosecond time scales. At these lengths and times quantum effects and atomistic details can not be neglected and the applicability of classical models is limited. Therefore, there is a need to develop new methodologies and computational tools for atomistic modeling of spin dynamics, in particular in the presence of electric currents. In this Thesis we construct a computational scheme, capable of describing the time evolution of spin systems both in isolation and under current-carrying conditions. The method has been developed in the spirit of the tightbinding model but it is transferable to more accurate first-principles methods such as density functional theory. This computational tool is then used to investigate timedependent phenomena in the systems of interest.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.